2020
DOI: 10.1088/2057-1976/abbbd5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity spectra of hepatic tumors reflect hepatocellular carcinoma progression in mice

Abstract: Background: Electrical impedance spectroscopy is a technique which evaluates differences in dielectric properties of tissues for cancer identification. Methods: Murine hepatic cancer model was developed by intraperitoneal administration of N-nitrosodiethylamine to male BALB/c mice. Tumors obtained were evaluated for their conductivity in frequency range of (4 Hz–5 MHz). All tumors were subjected to histopathological grading and parameters such as free spacing, necrosis, and cell density were estimated on histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…[75], [109]. In tissue analyses, like those performed by O'Rourke et al and Shetty et al, it was observed that tumors had higher conductivity than the surrounding liver, but supportive data is limited [66], [110]. Ultimately, extensive patient sampling is necessary to better understand presentations, particularly in the context of emerging pathophysiologies such as NAFLD.…”
Section: E Limitationsmentioning
confidence: 99%
“…[75], [109]. In tissue analyses, like those performed by O'Rourke et al and Shetty et al, it was observed that tumors had higher conductivity than the surrounding liver, but supportive data is limited [66], [110]. Ultimately, extensive patient sampling is necessary to better understand presentations, particularly in the context of emerging pathophysiologies such as NAFLD.…”
Section: E Limitationsmentioning
confidence: 99%